Sharon Ng COVID-19 Narrative - Ng, Sharon::::::::: (2021)
Sharon Ng's journal entry reflecting experiences during the COVID-19 pandemic. Ng describes the impact of Shelter-in-Place, such as the noticable decline in eyesight from device screen time, and the transition to remote work and study. Ng discusses spending habits and expresses disappointment in not being able to walk the stage for graduation.